Spatial Skyline Query Based on Surrounding Environment Untuk Data Streaming Menggunakan Apache-Spark - Firzatullah, Raden Muhamad; Djatna, Taufik; Annisa, Annisa; Andrianingsih, Andrianingsih (Jurnal Teknologi dan Sistem Komputer, 2022)
Previous research on Spatial Skyline Query Based on Surrounding Environment left a challenge in finding skyline objects that support the use of mobile devices. This study introduces a method that allows users to search for spatial objects dynamically. Cloud-based streaming data services are currently available to support the dynamic search of spatial skyline objects. Under these conditions, streaming data requires a longer processing time. This study aims to examine the effectiveness and efficiency of Apache-Spark in developing Spatial Skyline Query Based on Surrounding Environment in processing streaming data. Further implementation of the developed algorithm can provide better location access for users on mobile devices. Comparative analysis of algorithm execution time is performed by comparing algorithm processing on a single processor and cluster computing using various evaluation parameters. The test results on each parameter show that the computation time of the proposed algorithm on a single computation is not as good as the previous algorithm. However, in cluster computing, the proposed algorithm is superior